2001
DOI: 10.1086/320685
|View full text |Cite
|
Sign up to set email alerts
|

Disk Frequencies and Lifetimes in Young Clusters

Abstract: We report the results of the first sensitive L-band (3.5 micron) survey of the intermediate age (2.5 - 30 Myr) clusters NGC 2264, NGC 2362 and NGC 1960. We use JHKL colors to obtain a census of the circumstellar disk fractions in each cluster. We find disk fractions of 52% +/- 10%, 12% +/- 4% and 3% +/- 3% for the three clusters respectively. Together with our previously published JHKL investigations of the younger NGC 2024, Trapezium and IC 348 clusters, we have completed the first systematic and homogenous s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

128
1,615
9
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,664 publications
(1,774 citation statements)
references
References 34 publications
128
1,615
9
9
Order By: Relevance
“…We showed that an important consequence of including these effects is to drastically reduce the formation timescale (Alibert et al 2004) bringing it to an excellent agreement with the observationally derived lifetime of proto-planetary disks (Haisch et al 2001). The numerical tools we have developed, as well as the tests we have performed to validate them can be found in Alibert et al (2005a).…”
Section: Giant Planet Formation Modelsupporting
confidence: 61%
“…We showed that an important consequence of including these effects is to drastically reduce the formation timescale (Alibert et al 2004) bringing it to an excellent agreement with the observationally derived lifetime of proto-planetary disks (Haisch et al 2001). The numerical tools we have developed, as well as the tests we have performed to validate them can be found in Alibert et al (2005a).…”
Section: Giant Planet Formation Modelsupporting
confidence: 61%
“…Proper motions also provided membership information and a number of proto-planetary disk-bearing stars were revealed, yielding a disk fraction of 6% (Stolte et al 2010), similar to other massive young clusters throughout the Milky Way (e.g. Haisch et al 2001;Stolte et al 2006;Hernández et al 2007;Harayama et al 2008). This low disk fraction at 2.5 Myr shows that proto-planetary disk evolution, and possibly planet formation, are strongly modified in the environment of a massive cluster.…”
Section: The Arches and Quintuplet Clustersmentioning
confidence: 66%
“…For an unmagnetized disk, Tanaka et al (2002) showed that the protoplanet of 5M ⊕ located at 5AU and embedded in the minimum-mass solar nebula (Hayashi et al 1985) migrates inward in 8×10 5 years, which is shorter than the observed lifetime of a protoplanetary disk [∼ 10 7 years, see e.g., Haisch et al 2001].…”
Section: Introductionmentioning
confidence: 99%